Microbiome baseline for an Arctic sentinel: spatial patterning of nasal and anal microbiomes in ringed seals - Carlos A. Domínguez-Sánchez; Olwyn C. Friesen; Brent G. Young; Tera L. Edkins; Ellen V. Lea; Magali Houde; Stephen D. Petersen; David J. Yurkowski; Holly E. L. Gamblin; Steve H. Ferguson (Frontiers in Marine Science, 2026)
Introduction Ringed seals ( Pusa hispida ) are sentinel species of Arctic change, yet baseline microbiome data across their circumpolar range remain limited. Methods We profiled nasal and anal microbiomes from 90 free-ranging ringed seals across eight Arctic and sub-Arctic locations in Canada using 16S rRNA gene amplicon sequencing. Results Body site was the primary determinant of microbiome structure, with nasal and anal assemblages forming distinct communities that could be classified with 94.8% accuracy, consistent with strong niche partitioning. Nasal microbiomes exhibited a conserved core dominated by the genera Corynebacterium, Psychrobacter , and Suttonella across all sampling locations, supporting a stable respiratory baseline consistent with host-mediated filtering. In contrast, anal microbiomes showed higher richness, greater inter-individual variability, and a latitudinal gradient in diversity: Shannon index, Pielou’s evenness, and Simpson index all declined with increasing latitude (all p < 0.05), suggesting that ecological constraints at higher latitudes promote dominance by a narrower set of taxa without reducing overall richness. Despite overall compositional differences among locations, geographic distance was a poor predictor of microbiome dissimilarity in both body sites. Instead, continuous spatial gradients of latitude and longitude were associated with microbiome composition in both body sites: in nasal microbiomes, genus Corynebacterium increased while Ornithobacterium and Suttonella decreased at higher latitudes, whereas in anal microbiomes, Psychrobacter and Peptoclostridium increased northward while Fusobacterium and Bacteroides declined, patterns not previously reported in Arctic pinnipeds. Conclusion Together, these findings establish the first integrated nasal and anal microbiome baseline for ringed seals, demonstrate that the two body sites provide complementary ecological signals, and establish a reference framework for future microbiome-based health monitoring in a rapidly changing Arctic.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Biologging reveals rapid movements of harbour seals between freshwater and marine habitats in the subarctic - Katie R.N. Florko; David J. Yurkowski; C-Jae C. Breiter; Steven H. Ferguson; Holly E.L. Gamblin; Adam Grottoli; Andrea Nace; Courtney R. Shuert; Stephen D. Petersen (Frontiers in Marine Science, 2024)
Biologging tools can provide invaluable information on the movement and behaviour of animals, facilitating the elucidation of ecological dynamics, especially for wide-ranging species, and supporting conservation and management efforts. Harbour seals ( Phoca vitulina ) exhibit extensive habitat plasticity in their vast range across the northern hemisphere, with likely recent increases in abundance at northern latitudes, yet details of their movement behaviour in subarctic areas remain largely unknown. We used satellite-telemetry data, including nearly 5,000 locations and over 12,000 dives, obtained from six harbour seals tagged in western Hudson Bay from 2021 to 2023, to address the knowledge gap on their movement behaviour between marine and freshwater habitats in subarctic regions. We document the behavioural patterns, transit speeds, and diverse aquatic system usage, including detailed records of a harbour seal track traversing over 170 km upriver on three separate trips along the Seal River, Canada. Notably, we observed a rapid downstream transit from the Seal River to Hudson Bay, covering 214 km within a single day. Additionally, we highlight the prevalence of short dive durations in the Seal and Churchill Rivers, in contrast to longer dive durations in Hudson Bay. These insights complement existing evidence of harbour seal occurrences and river use at northern latitudes, as well as enhance our understanding of harbour seal movement ecology within Hudson Bay which can be used to better inform conservation and management strategies between connected freshwater and marine environments in the Arctic.

Trophic Structure and a Temporal Shift in Trophic Diversity of Mobile Consumers in a Subarctic Estuary - Jillian R. St. George; Stephen D. Petersen; James D. Roth; Steven H. Ferguson; David J. Yurkowski (Estuaries and Coasts, 2024)
Quantifying trophic relationships within and between species in terms of trophic position, ontogeny and trophic diversity provides information on community-level structure and function. Little attention has been focused on examining the trophic structure and temporal changes of communities in freshwater-marine coupled systems in the subarctic and associated impacts of anthropogenic activity on trophic interactions. Therefore, the objective of this study was to quantify the trophic position of mobile consumers (15 species in total) within the lower Churchill River area (Churchill, Manitoba, Canada), examine trophic position variation in relation to ontogeny, and measure the trophic diversity of a fish assemblage before (1993–1995) and after (2019–2020) the installation of the Churchill River weir in the late 1990s. We used stable isotopes (δ 13 C and δ 15 N) to quantify individual and group-level variation in trophic position of thirteen fish species and two seal species and also assessed six community-level metrics of a three fish species assemblage between time periods. Overall, species that mainly foraged on freshwater resources occupied lower trophic positions than species that mainly consumed marine resources. Trophic position increased with fish age only in cisco, fourhorn sculpin, Greenland cod and northern pike. A temporal shift from a trophically diverse to a more trophically redundant fish assemblage occurred between 1993–1995 and 2019–2020. As a result, these predator species now play similar trophic roles. Information on the long-term change in trophic structure of this sub-Arctic estuarine system may help with understanding how anthropogenic activity and climate change have influenced the trophic diversity of a fish assemblage inhabiting this system.

Habitat coupling dynamics of mobile consumers along a freshwater and marine resource gradient in a sub-Arctic estuarine system - Jillian R. St George; Stephen D. Petersen; James D. Roth; Steven H. Ferguson; David J. Yurkowski (Estuarine, Coastal and Shelf Science, 2023)

Novel observations of Atlantic walruses (Odobenus rosmarus rosmarus) in Archer Fjord, northern Ellesmere Island, Nunavut, Canada - David J. Yurkowski; Cody G. Carlyle; Uluriak Amarualik; Benjamin A. Lange; Andrew Platt; Jeff W. Higdon; D. Bruce Stewart; Adam Ferguson; Steven H. Ferguson; Christine Michel (Polar Biology, 2019)

Validating fin tissue as a non-lethal proxy to liver and muscle tissue for stable isotope analysis of yellow perch ( Perca flavescens ) - Meagan McCloskey; David J. Yurkowski; Christina A. D. Semeniuk (Isotopes in Environmental and Health Studies, 2018)

Coupled changes between the H‐Print biomarker and δ 15 N indicates a variable sea ice carbon contribution to the diet of Cumberland Sound beluga whales - T. A. Brown; E. Chrystal; S. H. Ferguson; D. J. Yurkowski; C. Watt; N. E. Hussey; T. C. Kelley; S. T. Belt (Limnology and Oceanography, 2017)
Sub‐Arctic habitats are being exposed to increasingly long periods of open water as sea ice continues to decline in thickness and extent. Some hypothesize that this will result in a reduction, and maybe total loss of sea ice derived (sympagic) carbon supply; however, the impact of such change on ecosystems requires further investigation. Here, we used the H‐Print biomarker approach that utilizes well‐defined indicators of both sympagic and phytoplanktic carbon, in combination with stable isotopes (δ 15 N), to study the effect of reducing sympagic carbon availability on beluga whales ( Delphinapterus leucas ) in the sub‐Arctic ecosystem of Cumberland Sound. Our data show that decreasing δ 15 N in belugas was negatively correlated with pelagic carbon (H‐Print) within their diet. We also identified a statistically significant ( R 2 = 0.82; p ≤ 0.01) change point in the proportion of sympagic/pelagic carbon within beluga around the year 2000, signified by consistently reducing δ 15 N, coupled with increasing pelagic carbon composition. This observed shift from sympagic to pelagic contribution to diet is likely to remain a feature of the Cumberland Sound ecosystem during the projected reduction of sea ice.

Distinct patterns of Arctic cod (Boreogadus saida) presence and absence in a shallow high Arctic embayment, revealed across open-water and ice-covered periods through acoustic telemetry - S. T. Kessel; N. E. Hussey; R. E. Crawford; D. J. Yurkowski; C. V. O’Neill; A. T. Fisk (Polar Biology, 2016)

Spatial and temporal variation of an ice-adapted predator’s feeding ecology in a changing Arctic marine ecosystem - David J. Yurkowski; Steven H. Ferguson; Christina A. D. Semeniuk; Tanya M. Brown; Derek C. G. Muir; Aaron T. Fisk (Oecologia, 2016)

H-Print: a new chemical fingerprinting approach for distinguishing primary production sources in Arctic ecosystems - T. A. Brown; D. J. Yurkowski; S. H. Ferguson; C. Alexander; S. T. Belt (Environmental Chemistry Letters, 2014)

Identifying variable sea ice carbon contributions to the Arctic ecosystem: A case study using highly branched isoprenoid lipid biomarkers in Cumberland Sound ringed seals - T. A. Brown; C. Alexander; D. J. Yurkowski; S. H. Ferguson; S. T. Belt (Limnology and Oceanography, 2014)
We analyzed liver samples from 322 ringed seals ( Pusa hispida ) collected from Cumberland Sound (southeast Baffin Island) to test our ability to differentiate between carbon sources in near apex predators. Highly branched isoprenoids (HBIs) were present in all samples, and their distributions were consistent with recognized seal habitat use. HBI distributions in mature seals (≥ 5 yr) confirmed a less variable carbon source during winter, consistent with geographically restricted sexually mediated territorialism. In contrast, HBI distributions were more variable for immature seals (